Intermediate accounting - Stice, James D.; Stice, Earl K. (Cengage Learning, 2014)
Presents an approach combined with the necessary coverage of GAAP, codification, and IFRS to help you understand accounting in terms of what goes on in a business. This title offers core concepts of accounting principles with procedural applications